IMPROVING THE ACCOUNTING AND AUDIT OF CURRENT ASSETS - Mavlanova Dilrabo Uktamovna (Modern American Journals, 2025)
This article explores theoretical foundations, current practices, and proposed improvements in the accounting and audit of current assets. The research analyzes international standards, accounting principles, and audit procedures related to assets such as cash, inventory, and receivables. Special attention is given to risk-based auditing and digital technologies used in asset management.
Keywords: Current assets, accounting, audit, cash, receivables, inventory, financial reporting, internal control, audit standards, transparency.